(130) Elektra Delta - on the stability of the new third moonlet - Valvano, G. [UNESP]; Oliveira, R. Machado [UNESP]; Winter, O. C. [UNESP]; Sfair, R. [UNESP]; Borderes-Motta, G. (Oxford University Press (OUP), 2023)
The aim of this work is to verify the stability of the proposed orbital solutions for the third moonlet (Delta) taking into account a realistic gravitational potential for the central body of the quadruple system (Alpha). We also aim to estimate the location and size of a stability region inside the orbit of Gamma. First, we created a set of test particles with intervals of semimajor axis, eccentricities, and inclinations that covers the region interior to the orbit of Gamma, including the proposed orbit of Delta and a wide region around it. We considered three different models for the gravitational potential of Alpha: irregular polyhedron, ellipsoidal body, and oblate body. For a second scenario, Delta was considered a massive spherical body and Alpha an irregular polyhedron. Beta and Gamma were assumed as spherical massive bodies in both scenarios. The simulations showed that a large region of space is almost fully stable only when Alpha was modelled simply as an oblate body. For the scenario with Delta as a massive body, the results did not change from those as mass-less particles. Beta and Gamma do not play any relevant role in the dynamics of particles interior to the orbit of Gamma. Delta's predicted orbital elements are fully unstable and far from the nearest stable region. The primary instability source is Alpha's elongated shape. Therefore, in the determination of the orbital elements of Delta, it must be taken into account the gravitational potential of Alpha assuming, at least, an ellipsoidal shape.
Keywords: asteroids: general; celestial mechanics; minor planets; planets and satellites: dynamical evolution and stability